Strong μ‐faster convergence and strong μ‐acceleration of convergence by regular matrices - Aasma, Ants (Mathematical Modelling and Analysis, 2008)
The present paper continues the study of acceleration of convergence started in the paper [A. Aasma, Proc. Estonian Acad. Sci. Phys. Math., 2006, 55, 4, 195–209]. The new, non‐classical convergence acceleration concept, called strong μ‐acceleration of convergence (μ is a positive monotonically increasing sequence), is introduced. It is shown that this concept allows to compare the speeds of convergence for a larger set of sequences than the classical convergence acceleration concept. Regular matrix methods are used to accelerate the convergence of sequences.First Published Online: 14 Oct 2010